Relationship between rheological properties and transverse relaxation time (T2) of artificial and porcine vitreous humour. (May 2020) - Thakur, Sachin S.; Pan, Xingzheng; Kumarasinghe, Gamith L.; Yin, Naibo; Pontré, Beau P.; Vaghefi, Ehsan; Rupenthal, Ilva D.
Abstract: Vitreous liquefactive processes play an integral role in ocular health. Knowledge of the degree of liquefaction would allow better monitoring of ocular disease progression and enable more informed therapeutic dosing for an individual patient. Presently this process cannot be monitored in a non-invasive manner. Here, we evaluated whether magnetic resonance imaging (MRI) could predict the viscoelasticity and in turn liquefactive state of artificial and biological vitreous humour. Gels comprising identical concentrations of hyaluronic acid and agar ranging from 0.125 to 2.25 mg/ml of each polymer were prepared and their T2 was measured using a turbo-spin echo sequence via 3T clinical MRI. The gels were subsequently subjected to rheological frequency and flow sweeps and trends between T2 and rheological parameters were assessed. The relationship between T2 and vitreous humour rheology was further assessed using ex vivo porcine eyes. An optimised imaging technique improved homogeneity of obtained artificial vitreous humour T2 maps. Strong correlations were observed between T2 and various rheological parameters of the gels. Translation to porcine vitreous humour demonstrated that the T2 of biological tissue was related to its viscoelastic properties. This study shows that T2 can be correlated with various rheological parameters within gels. Future investigations will assess the translatability of these findings to live models. Highlights: MRI protocol optimisation allows acquisition of homogenous T2 maps of artificial vitreous humour. Artificial vitreous humour T2 can be correlated with viscoelastic properties of the gel. An optimised MRI protocol can non-invasively identify regional variations in T2 within porcine vitreous humour .